ISLAM AND THE IMAGE OF MUSLIMS IN WESTERN MEDIA: REALITY OR BIAS - Naheed Razia (Journal of Religion and Society, 2025)
Western media has played a significant role in fueling "Islamophobia" by adopting various strategies to portray a negative image of Muslims. It often associates them with extremism, violence, and lack of integration, thereby distorting their true identity. Such portrayals have contributed to widespread misconceptions, fostering fear and prejudice against Muslims on a global scale. These biased representations not only shape public perceptions but also influence political policies and social interactions, further marginalizing Muslim communities. The aim of this study is to analyze how Western media represents Muslims and what impact this portrayal has on public opinion and societal structures. The research examines how Muslims are frequently depicted as uncivilized, violent, and socially isolated, reinforcing stereotypes that fail to acknowledge the diversity and richness of Islamic cultures. Furthermore, the study highlights the need for a comprehensive and positive narrative that accurately represents Islam and its followers. Addressing this issue requires a more balanced media approach that fosters cross-cultural understanding rather than division. A well-balanced representation can help reduce misunderstandings, bridge gaps between different communities, and promote a more harmonious global society. Keywords: Islam, Muslims, Image, Western Media, Reality or Bias, Islamophobia, Stereotypes, Misrepresentation, Media Influence